Kinetic origami surfaces: from simulation to fabrication - Osório, F. (2018)
On nowadays social, technological and economic context everything changes constantly so there is the persistent need to adapt at all levels. This research defends that Architecture should do the same through the use of kinetic and interactive buildings, or elements in a building. These elements should allow the building to adapt to changing needs and conditions. This article describes the current state of an ongoing research that proposes the use of kinetic Rigid Origami foldable surfaces to be used as roofs for spaces with big spans and the practical contribution that the Design Studio Surfaces INPLAY has brought to it.